New report of two patients with mosaic trisomy 9 presenting unusual features and longer survival - Zen, Paulo Ricardo Gazzola; Rosa, Rafael Fabiano Machado; Rosa, Rosana Cardoso Manique; Graziadio, Carla; Paskulin, Giorgio Adriano (São Paulo Medical Journal, 2011)
CONTEXT: Mosaic trisomy 9 is considered to be a rare chromosomal abnormality with limited survival. Our objective was to report on two patients with mosaic trisomy 9 presenting unusual findings and prolonged survival. CASE REPORTS: The first patient was a boy aged six years and five months presenting weight of 14.5 kg (< P3), height of 112 cm (P10), head circumference of 49 cm (P2), prominent forehead, triangular and asymmetric face, thin lips, right microtia with overfolded helix, small hands, micropenis (< P10), small testes and hallux valgus. His lymphocyte karyotype was mos 47,XY,+9[4]/46,XY[50]. Additional cytogenetic assessment of the skin showed normal results. The second patient was a two-year-old girl who was initially assessed at five months of age, when she presented weight of 5.3 kg (< P3), height of 61.5 cm (P2-P10), head circumference of 40.5 cm (P25), sparse hair, micrognathia, right ear with overfolded helix and preauricular pit, triphalangeal thumbs and sacral dimple. She also had a history of congenital heart disease, hearing loss, hypotonia, delayed neuropsychomotor development and swallowing disorder. Her lymphocyte karyotype was mos 47,XX,+9[3]/46,XX[69]. Both patients had unusual clinical findings (the first, hemifacial hypoplasia associated with microtia, with a phenotype of oculo-auriculo-vertebral spectrum, and the second, triphalangeal thumbs and hearing loss) and survival greater than what is usually described in the literature (< 1 year). Further reports will be critical for delineating the clinical features and determining the evolution of patients with mosaic trisomy 9.